Filipino heritage : the making of a nation. ([n.p.] : Lahing Pilipino Pub, 1977)
Contents: -v.1. The Stone Age in the Philippines; the search for Early Man.-v.2. The Metal Age in the Philippines; the foundations of the society.-v.3. The age of trade and contacts; visitors from across many seas.-4. The Spanish colonial period (16th century); the day of the conquistador. -v.5. The Spanish colonial period (17th/18th centuries) -v.6. The Spanish colonial period (18th/19th centuries)